Исследование мутагенности и генотоксичности питьевой воды - Гончарук, В.В.; Верголяс, М.Р.; Болтина, И.В. (Химия и технология воды, 2013)
Проведен анализ генотоксических и мутагенных свойств фасованной питьевой воды с использованием клеток различных тест-объектов. Показана эффективность применения комплексных исследований для более точной оценки качества воды. Проведений аналіз генотоксичних та мутагенних властивостей фасованої питної води з використанням кліток різних тест-объектів. Показана ефективність застосування комплексних досліджень для більш точної оцінки якості води. Has been analyzed genotoxic and mutagenic packaged drinking water with using cells as test organisms and cell cultures of human peripheral blood. Revealed persistent correlation between the majority of indicators identified on fishes, onions, and the number of aberrant damaged metaphases with metabolic activation. The result shows the effectiveness of the comprehensive research to better assess the quality of water.